Interocular Shift of Visual Attention Enhances Stereopsis and Visual Acuities of Anisometropic Amblyopes beyond the Critical Period of Visual Development: A Novel Approach - Liwen Huang; Xinghuai Sun; Gang Luo; Shuai Liu; Rui Liu; Behzad Mansouri; Vicky wing lai Wong; Wen Wen; Hong Liu; Ai-Hou Wang (Journal of Ophthalmology)
Aims. Increasing evidence shows that imbalanced suppressive drive prior to binocular combination may be the key factor in amblyopia. We described a novel binocular approach, interocular shift of visual attention (ISVA), for treatment of amblyopia in adult patients. Methods. Visual stimuli were presented anaglyphically on a computer screen. A square target resembling Landolt C had 2 openings, one in red and one in cyan color. Through blue-red goggles, each eye could only see one of the two openings. The patient was required to report the location of the opening presented to the amblyopic eye. It started at an opening size of 800 sec of arc, went up and down in 160 sec of arc step, and stopped when reaching the 5th reversals. Ten patients with anisometropic amblyopia older than age 14 (average age: 26.7) were recruited and received ISVA treatment for 6 weeks, with 2 training sessions per day. Results. Both Titmus stereopsis (z=-2.809, P=0.005) and Random-dot stereopsis (z=-2.317, P=0.018) were significantly improved. Average improvement in best corrected visual acuity (BCVA) was 0.74 line (t=5.842, P<0.001). Conclusions. The ISVA treatment may be effective in treating amblyopia and restoring stereoscopic function.